Influences of Zn Concentration on Dielectric Properties of ZnxNi1-xFe2O4 Magnetic Nanoparticles - Suharyadi, Edi; Rahayu, Dwi Indah; Armitasari, Linda; Abraha, Kamsul (Makara Journal of Science, 2018)
Dielectric properties of ZnxNi1-xFe2O4magnetic nanoparticles (MNPs) with various Zn concentration (x = 0.2-0.8) havebeen investigated over a wide frequency range 5–120 kHz. Zn-Ni ferriteMNPs have spinel cubic structure. Thecrystallite size of the sample for x = 0.2 was about 21.5 nm and then decreases by increasing Zn concentration. For sample with x = 0.4 at frequency 20 kHz, the real dielectric constant (ε') was 35.9, imaginary dielectric constant (ε") was 20.4 and loss tangent (tanδ) was 0.6. Zn concentration would affect to availability of ferrous and ferric ions in the octahedral site which are preferentially occupied by Zn2+ion. The dielectric constants decrease with increasing frequency. The sample with at x = 0.6 has thehighest dielectric on frequency 5 kHz. The maximum AC conductivity(σAC) was 1.7 x 10-4 Ω-1 at 65 kHz observed for concentration x = 0.3. The dielectric constants and conductivity at low frequency are due to the existence of grains boundary while the dispersion in the high frequency region are due to the conducting grains.